Satisfaction of Postgraduate Students of Kerman University of Medical Sciences Iran with their Training Program and Campus Facilities - Ali Akbar Haghdoost; Ali Akbar Haghdoost; Hossein Rafiei; Abozar Raeisvandi; Yasan Kazemzadeh (Kerman University of Medical Sciences, 2015)
Background & Objective: Higher education and postgraduate programs characterize one of the key components of human development in any country The present study was carried out at Kerman University of Medical Sciences Iran with the aim of investigating MSc and PhD students level of satisfaction with their present situation and their view of the amount of attention and effort the university authorities exercise to meet the students expectations   Methods: The target population of the present descriptive analytical study consisted of 135 postgraduate students of Kerman University of Medical Sciences Data were gathered using the Student Satisfaction Inventory (SSI) This inventory evaluates the students satisfaction with services provided by supervisors and educational educational assistance campus facilities studentcentered and general services   Results: In total 422% of students (41% male and 432% female) were satisfied with the services The maximum level of satisfaction of students was with services provided by supervisors and the lowest level was with campus facilities On the other hand 383% of students (36% male and 419% female) were satisfied with the amount of attention from the university authorities to the services In their view maximum attention was given to the services provided by supervisors and the minimum was given to campus facilities   Conclusion: In conclusion students level of satisfaction with their current situation and the level of effort made by authorities to meet their needs were rated low In view of the growing increase in admittance of students into higher education and to promote the quality of this sector university authorities should pay more heed to meeting the needs of postgraduate students who play a significant role in building the countrys future